INTEREST GROUP SESSION - NURSING CARE OF OLDER ADULTS: ESPO/ HEALTH SCIENCES SECTION SYMPOSIUM: AFRICAN AMERICAN FAMILY DEMENTIA CAREGIVERS—A PURPOSE OF LONGER LIVES. (11th November 2018) - Lopez, R; Rose, K
Abstract: Nearly 16 million family caregivers provide essential care to 5.5 million Americans living with Alzheimer's and related dementias (ADRD). African Americans are two to three times more likely to have ADRD than non-Hispanic whites, to be caregivers at a younger age, and to provide higher intensity care. The purpose of this symposium is to increase understanding of family caregiving from the perspective of African American family caregivers. Dr. Epps will open the symposium by presenting the results of a qualitative study that characterized African American family networks and the themes of complexity, familism, and religiosity. Dr. Moss will report on her study of health-related quality of life and family caregivers' self-efficacy for surrogate decision making. She will discuss the complex interplay between their perceptions of quality of life and their ability to make end-of-life decisions. Ms. Bonds will also report on her study in which she used multilevel modeling and found significant relationships between perceived levels of involvement in decision making, quality of life, and dyadic strain. Dr. McLennon will present findings from her mixed methods study regarding cultural variations in perceptions among older African American caregivers to assess burden and find meaning through caregiving. Thereafter, Dr. Brewster will draw attention to the importance of sleep among African American caregivers and report on two interventions to enhance sleep quality. To conclude the symposium, the researchers will discuss the role of race in researcher-participant relationships and its impact on recruitment, data collection, analysis, interpretation, and dissemination of their findings.